Uncovering the shared lipidomic markers of subclinical osteoporosis-atherosclerosis comorbidity: The Young Finns Study - Mishra Binisha H; Mishra Pashupati P; Mononen Nina; Hilvo Mika; Sievänen Harri; Juonala Markus; Laaksonen Marika; Hutri-Kähönen Nina; Viikari Jorma; Kähönen Mika; Raitakari Olli T; Laaksonen Reijo; et al. (ELSEVIER SCIENCE INC, 2022)
Background: Osteoporosis and atherosclerosis are complex multifactorial diseases sharing common risk factors and pathophysiological mechanisms suggesting that these are comorbidities. Omics studies identifying joint molecular markers associated with these diseases are sparse.
Subjects and methods: Using liquid chromatography-tandem mass spectrometry, we quantified 437 molecular lipid species from the Young Finns Study cohort (aged 30-45 years and 57% women) and performed lipidomewide multivariate analysis of variance (MANOVA) with early markers for both diseases. Carotid intima-media thickness for atherosclerosis measured with ultrasound and bone mineral density from distal radius and tibia for osteoporosis measured with peripheral quantitative computed tomography were used as early markers of the diseases.
Results: MANOVA adjusted with age, sex and body mass index, identified eight statistically significant (adjusted p-value (padj) < 0.05) and 15 suggestively significant (padj < 0.25) molecular lipid species associated with the studied markers. Similar analysis adjusted additionally for smoking habit, physical activity and alcohol consumption identified four significant and six suggestively significant molecular lipid species. These most significant lipid classes/species jointly associated with the studied markers were glycerolipid/TAG(18:0/18:0/18:1), glycerophospholipid/PC(40:3), sphingolipid/Gb3(d18:1/22:0), and sphingolipid/Gb3(d18:1/24:0).
Conclusion: Our results support the osteoporosis-atherosclerosis comorbidity hypothesis and present potential new joint lipid biomarkers for these diseases.